PERSEPSI ORANG TUA TENTANG BERMAIN DENGAN TINGKAT KECEMASAN PADA ANAK USIA 2-5 TAHUN - Rischa Devi Hayuningtyas; Novia Choirun Nadia (Jurnal Delima Harapan, 2022)
Anxiety is a state of restlessness that is not clear which is often experienced by children undergoing therapy in the hospital. Anxiety in children during hospitalization is at risk of disrupting the child's growth and development and delaying the recovery process. Play is a solution to reduce anxiety and activities that can change behavior, stimulate children's development, and support the healing process, so that children become more cooperative. The purpose of this study was to determine the Correlation between parents' perceptions about playing and anxiety levels in children aged 2-5 years in Soka Room B RSUD dr. Darsono, Pacitan Regency This type of research is quantitative. with a purposive sampling technique A total of 24 respondents. Data analysis using spearman rank test. The results showed that there was a relationship between parents' perceptions about playing with the level of anxiety in children aged 2-5 years in Soka Room B RSUD dr. Darsono Pacitan Regency with p value = 0.000 (p < 0.05). Parents' perceptions about playing are needed to reduce the level of anxiety in children aged 2-5 years in the recovery process.